Calcined seed crystal activity detection and evaluation method
By using a nanoparticle size meter to detect the particle size data of the calcined seed crystal, the problems of long time, complex equipment and high cost in the prior art are solved, and convenient, efficient and accurate activity detection effects are achieved.
Patent Information
- Application Number
- CN202411839238.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The existing calcined seed activity detection methods are time-consuming, sophisticated and complex equipment are high in investment costs, which cannot fully reflect the activity level of calcined seeds.
The particle size data of the calcined seed crystals were detected by a nanoparticle size meter and its activity was evaluated based on the particle size data. The method includes the sample preparation step, adding water to the calcined seed crystals, then ultrasonic pulverizing through a cell pulverizer to obtain the sample liquid; then using a nanoparticle size meter to obtain the particle size data of the calcined seed crystals.
The method is convenient to operate, has high detection efficiency, accurate results, good stability, low equipment cost, and can accurately evaluate the activity of calcined seeds, which is suitable for practical production applications.
Smart Images

Figure CN119715272A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of calcined crystal seed detection, and in particular to a method for detecting and evaluating the activity of calcined crystal seeds. Background Art
[0002] The main function of calcined seeds in the production process of titanium dioxide by sulfuric acid is to induce metatitanic acid to convert into rutile type, reduce calcination temperature, and improve pigment performance. In the production of rutile titanium dioxide by sulfuric acid, titanium liquid (titanic acid sulfate) generally uses self-generated seeds or external seeds of titanic acid sulfate to form nuclei. After hydrolysis to form metatitanic acid, it is filtered, washed, added with calcined seeds, treated with salt, and calcined to form rutile titanium dioxide with certain pigment properties. The calcined seeds can not only promote the conversion of the product to rutile type during calcination, but also improve the pigment properties of the product such as color reduction power and hue, and improve the particle shape during calcination, making the particles smooth, soft and not easy to sinter.
[0003] At present, the commonly used basis for judging the activity of calcined seed crystals is to use an X-ray diffractometer to detect the rutile content of the calcined material. The rutile content is the activity level. However, in actual production, it is found that the rutile content cannot fully reflect the activity level of the calcined seed crystals, and the method is time-consuming, the equipment required is sophisticated and complex, and the investment cost is high. Summary of the invention
[0004] The purpose of the present application is to provide a method for detecting and evaluating the activity of calcined seed crystals, which has the advantages of convenient operation, high detection efficiency, accurate results, good stability, low equipment cost, and is conducive to actual production application.
[0005] The technical solution of this application is as follows:
[0006] The present application provides a method for detecting and evaluating the activity of calcined seed crystals, which comprises the following steps:
[0007] Sample preparation: take the calcined seed crystals and place them in a container, add water to prepare a feed solution, and then use a cell crusher to ultrasonically crush the feed solution to obtain a sample solution;
[0008] Sampling: Pipette the sample liquid and drop it into a centrifuge tube, add water to the centrifuge tube to adjust the concentration, and then use a nanoparticle size analyzer to test to obtain the calcined seed crystal particle size data, and evaluate the calcined seed crystal activity based on the obtained particle size data.
[0009] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0010] In view of the above aspects, the embodiment of the present application provides a method for detecting and evaluating the activity of calcined seed crystals, which first prepares the sample, adds water to the calcined seed crystals to prepare a liquid of a certain concentration, and then uses a cell crusher to ultrasonically crush the liquid to obtain a sample liquid. Then, the sample liquid is used as the sample to be tested, and the sample liquid is dripped into a centrifuge tube, and water is added to adjust the concentration so that the concentration reaches a concentration suitable for detection by a nanoparticle size analyzer, and then the nanoparticle size analyzer is directly used for detection to obtain its particle size data, and finally the activity of the measured calcined seed crystals is evaluated according to its particle size data.
[0011] Among them, the detection equipment nanoparticle size analyzer is simple to operate and easy to use, has a wide range of applications, can accurately and intuitively characterize the size of the calcined seed particle size, and its error is usually less than 5nm. According to the experimental results of the present application scheme, after detection, the calcined seeds with larger particle size data have relatively lower calcination activity, and as the calcined seed particle size data gradually increases, its calcination activity also gradually decreases. Therefore, the present application scheme can be used to detect the particle size of different calcined seeds, and the relative activity between different calcined seeds can be evaluated by comparison; or a series of data curve models of different particle sizes and calcination activities can be established. When facing calcined seeds with unknown particle sizes, they can be directly detected and their particle size data can be brought into the curve model to evaluate their calcination activity.
[0012] Furthermore, in some embodiments of the present application, in the above-mentioned sample preparation step, the titanium concentration in the slurry is 0.3-1%.
[0013] Furthermore, in some embodiments of the present application, in the above sample preparation step, the titanium concentration in the slurry is 0.4%.
[0014] In the above embodiment, the feed solution (seed solution) with a titanium concentration of 0.4% can be better adjusted in the subsequent steps to reach the concentration requirement suitable for the nanoparticle size analyzer, and the ultrasonic dispersion effect is better and the test result is more accurate.
[0015] Furthermore, in some embodiments of the present application, in the above sample preparation step, the feed liquid is ultrasonically pulverized by a cell pulverizer at 20°C.
[0016] Furthermore, in some embodiments of the present application, in the above-mentioned sample preparation step, when ultrasonic crushing is performed, the ultrasonic conditions are: a single ultrasonic time of 5 s, an interval time of 1 s, and a power of 40%.
[0017] Furthermore, in some embodiments of the present application, in the above-mentioned sample preparation step, when ultrasonic pulverization is performed, the total ultrasonic time is 20 to 30 minutes.
[0018] Furthermore, in some embodiments of the present application, in the above-mentioned sample preparation step, when ultrasonic crushing is performed, the total ultrasonic time is 20 minutes.
[0019] In the above embodiments, according to the experimental findings of the present application, after the total ultrasonic time reaches 20 minutes, the particle size data of the obtained sample liquid after being tested by the nanoparticle size analyzer will tend to be stable; the difference between the particle size data obtained by the final processed sample liquid when the total ultrasonic time is 20 minutes and the total ultrasonic time is 30 minutes is usually less than 2 nm; the difference between the particle size data of the sample liquid obtained when the total ultrasonic time is 30 minutes and the total ultrasonic time is 40 minutes is usually less than 1 nm; and after the total ultrasonic time exceeds 40 minutes, for example, the total ultrasonic time is 40 minutes and the total ultrasonic time is 60 minutes, there is almost no difference in the particle size data between the sample liquids obtained; therefore, taking into account the detection time, efficiency and accuracy, the present application adopts a total ultrasonic time of 20 to 30 minutes, preferably 20 minutes.
[0020] Furthermore, in some embodiments of the present application, in the above-mentioned sample measurement step, the sample liquid is aspirated and dropped 2 drops into a centrifuge tube, and then water is added into the centrifuge tube to adjust the concentration to a suitable concentration for the nanoparticle size analyzer.
[0021] Furthermore, in some embodiments of the present application, the water is desalted water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a curve chart of the particle size detection results of the calcined seed crystals in the test example of this application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0025] It should be noted that the term "include" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0027] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0028] Example 1
[0029] The present application provides a method for detecting and evaluating the activity of calcined seed crystals, which comprises the following steps:
[0030] Sample preparation: Take 2 g of calcined seed crystals with a titanium concentration of about 10%, place them in a 100 mL clean beaker, add 50 g of desalted water to prepare a feed solution with a titanium concentration of about 0.4%;
[0031] The cell crusher was set to perform ultrasonic crushing on the liquid by setting the single ultrasonic time to 5s, the interval time to 1s, the temperature to 20°C, the power to 40%, and the total ultrasonic time to 20min to obtain the sample liquid;
[0032] Sampling: Use a rubber-tipped dropper to absorb the sample liquid, drop 2 drops into a centrifuge tube, add desalted water to the centrifuge tube to adjust the concentration to the appropriate concentration for the nanoparticle size analyzer, and then use the nanoparticle size analyzer to test and obtain the calcined seed crystal particle size data, the average particle size of which is 72nm.
[0033] Example 2
[0034] This embodiment is based on embodiment 1, and the difference from embodiment 1 is that calcined seeds of different particle sizes are used, and the remaining method steps and conditions are the same as those of embodiment 1;
[0035] After testing by a nanoparticle size analyzer, the average particle size is 157nm.
[0036] Example 3
[0037] This embodiment is based on embodiment 1, and the difference from embodiment 1 is that calcined seeds of different particle sizes are used, and the remaining method steps and conditions are the same as those of embodiment 1;
[0038] After testing by a nanoparticle size analyzer, the average particle size is 175.6nm.
[0039] Test Example 1
[0040] During calcination, calcination seeds of different particle sizes (referring to the particle size data obtained by detection according to the embodiment of the present application) were added in an amount of 3%, and salt treatment was performed according to the same procedure;
[0041] By adjusting the calcination temperature, the rutile content of the calcined material is ensured to be consistent. The calcination temperature and the black slurry b value of the calcined material are compared. The results are shown in Table 1:
[0042] Table 1
[0043]
[0044] The black slurry b value is a measure of whiteness, indicating the ability to present white color, and is related to the particle size distribution. As can be seen from Table 1, under the premise of the same calcined seed addition amount and the same rutile content, as the calcined seed particle size increases, the black slurry b value of the calcined material continues to increase, and the calcination temperature gradually increases. This shows that the larger the calcined seed particle size, the weaker the promoting effect on the conversion of rutile titanium dioxide during calcination. Conversely, the smaller the particle size of the calcined seed, the lower the calcination temperature after addition, and the lower the black slurry b value, indicating that it is more active.
[0045] It can be seen that the particle size of the calcined seeds and the activity of the calcined seeds in promoting conversion have a consistent rule, which is that the larger the particle size data, the larger the black slurry b value, and the weaker the calcination activity; the smaller the particle size data, the smaller the black slurry b value, and the stronger the calcination activity.
[0046] Test Example 2
[0047] The calcined seed particle size curves and results obtained in Examples 1 to 3 of the present application are as follows: Figure 1 And as shown in Table 2.
[0048] Table 2
[0049] Calcination Seed Example 1 Example 2 Example 3 Average particle size / nm 72 157 175.6
[0050] Based on the conclusion of Experimental Example 1, Examples 1 to 3 of the present application are further verified:
[0051] The same type of calcined seeds as in Examples 1 to 3 were respectively used, and the particle size data thereof were detected according to the scheme of the present application, and the specific surface area and the conversion rate of the calcined seeds were further detected;
[0052] Using these three calcined seeds respectively, in the same manner as in Experimental Example 1, under the same addition amount and the same rutile content of the calcined material, the calcination temperature and black slurry b value data were compared. The results are shown in Table 3:
[0053] Table 3
[0054]
[0055]
[0056] It can be seen from Table 3 that the particle size of the calcined seeds of Examples 1 to 3 gradually increases, and their specific surface areas gradually decrease; there are obvious differences among the three calcined seeds, and the conversion rates of the three calcined seeds are quite different.
[0057] Using the calcined seeds in Examples 1 to 3, calcination tests were carried out under the conditions of the same addition amount and the same rutile content of the material after calcination. It can be seen that there is an obvious regularity between the particle size of the calcined seeds and the calcination temperature and the b value of the black slurry, and it is consistent with the conclusion drawn in Experimental Example 1, indicating that the results of the calcined seeds activity detection and evaluation method of the present application are reliable; while the rutile conversion rate of the calcined seeds has no obvious correlation with the quality of the material after calcination, indicating that the activity evaluation of the calcined seeds based on the calcined seeds conversion rate or the rutile content of the material after calcination is not necessarily reliable.
[0058] According to the test conclusions, the activities of the calcined seeds of Examples 1 to 3 were evaluated. It can be seen that among the three calcined seeds, the calcined seeds of Example 1 had the best activity, and the calcined seeds of Example 3 had the worst activity.
[0059] In summary, the embodiment of the present application provides a method for detecting and evaluating the activity of calcined crystal seeds, and the nanoparticle size analyzer of the detection device is simple and easy to use, has a wide range of applications, can accurately and intuitively characterize the size of the calcined crystal seed particle size, and its error is usually less than 5nm. According to the experimental results of the present application scheme, after detection, the calcined crystal seeds with larger particle size data have relatively lower calcination activity, and as the calcined crystal seed particle size data gradually increases, its calcination activity also gradually decreases. Thus, the present application scheme can be used to detect the particle size of different calcined crystal seeds, and the relative high and low activities between different calcined crystal seeds can be evaluated by comparison; or a series of data curve models of different particle sizes and calcination activities can be established. When facing calcined crystal seeds of unknown particle size, they can be directly detected and their particle size data can be brought into the curve model to evaluate their calcination activity. Its detection method is convenient to operate, has high detection efficiency and accurate results, good stability, low equipment cost, and is conducive to actual production applications.
[0060] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A method for detecting and evaluating the activity of calcined seed crystals, characterized in that: It includes the following steps: Sample preparation: take the calcined seed crystals and place them in a container, add water to prepare a feed solution, and then use a cell crusher to ultrasonically crush the feed solution to obtain a sample solution; Sampling: Pipette the sample liquid and drop it into a centrifuge tube, add water to the centrifuge tube to adjust the concentration, and then use a nanoparticle size analyzer to test to obtain the calcined seed crystal particle size data, and evaluate the calcined seed crystal activity based on the obtained particle size data.
2. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: In the sample preparation step, the titanium concentration in the feed solution is 0.3-1%.
3. The method for detecting and evaluating the activity of calcined seed crystals according to claim 2, characterized in that: In the sample preparation step, the titanium concentration in the feed solution is 0.4%.
4. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: In the sample preparation step, the feed solution is ultrasonically crushed by a cell crusher at 20°C.
5. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: In the sample preparation step, when ultrasonic pulverization is performed, the ultrasonic conditions are: a single ultrasonic time of 5 s, an interval time of 1 s, and a power of 40%.
6. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: In the sample preparation step, when ultrasonic pulverization is performed, the total ultrasonic time is 20 to 30 minutes.
7. The method for detecting and evaluating the activity of calcined seed crystals according to claim 6, characterized in that: In the sample preparation step, when ultrasonic pulverization is performed, the total ultrasonic time is 20 minutes.
8. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: In the sample measurement step, the sample liquid is drawn and dropped 2 drops into a centrifuge tube, and then water is added into the centrifuge tube to adjust the concentration to a suitable concentration for the nanoparticle size analyzer.
9. The method for detecting and evaluating the activity of calcined seed crystals according to claim 1, characterized in that: The water is desalted water.